Pelaksanaan Perjanjian Pinjam Meminjam Uang Non-Kontraktual Dengan Jaminan Benda Bergerak(Studi Perlindungan Hukum Yang Proporsional Bagi Para Pihak) - Bariah, Ummu, Septarina Budiwati, S.H., M.H, Darsono, S.H., M.Hum (2016)
The purpose of this research is to investigate the implementation of the agreement of non-contractual lending and borrowing money to bail moving objects, to determine the legal protection that is proportional to the parties in the agreement of non-contractual lending and borrowing money and to know the problems that arise. The method used in this research is empirical juridical with descriptive research. The data source consists of primary data, from interviews and secondary data, consist of legal data primary, secondary and tertiary. Data were collected from literature study, interview and observation. Then the data were analyzed qualitatively. The results of the research showed that the implementation of the agreement non-contractual lending and borrowing money by using collateral moving objects are in accordance with the law, as long as both parties agree with a good faith. Appropriate legal protection for both parties is there is a protection of both preventive and repressive. There are some problems caused by the existence of the agreement, such as debtors who do not pay the loan on time, have past the time limit but make reasons that not have any money, was already paid but was deemed not yet paid by the creditor, collateral moving objects that have been used by the creditors even if the debtor has not been declared in default or bankruptcy, and the guarantee of moving objects that are not well maintained when in the creditors place.